PERANCANGAN APLIKASI PENJUALAN PAKAIAN PADA AMITEA COLLECTION BERBASIS WEBSITE - Anton Putra Pratama (2023)
The rapid development of information technology has made many stores Initially selling offline is now moving to online. Because The development of this technology has a good impact on business run. Amitea Collection is a home-based business that sells clothes and still makes purchases manually. Based on this, the author will design and also build a website-based information system to facilitate the work of the Amitea Collection in carrying out the service, purchasing process and also providing realtime information between the shop and the buyer. The method used by the author is the Waterfall Method with problem identification using the PIECES method, PHP programming language using the CodeIgniter framework, the database used is MySQL and ending with a trial test using black box testing. With the development of this website-based application, Amitea Collection has been able to perform sale and servicing with ease.